The moving and shifting concept of culture - Järviluoma-Mäkelä, Helmi (Approaching Religion, 2011)
Today, anthropologists, ethnomusicologists, cultural, and gender scholars are interested in culture not only as it is performed, but as it is continuously done, constructed, maintained through acting, musicking, talking, dancing together. Culture lives, and its elements—or aspects, if you wish—are constantly converging, and articulating into new, moving and shifting formations. In this paper Järviluoma discusses the different ways of understanding the concept of culture, interweaving the ideas with the early twentieth century forms of music making in her own grandmother’s home village in northern Finland. She discusses how the new ‘culture’, within the ‘civilising’ social movements converged with the old ways of life and musicking.